HISTORICAL GEOGRAPHICAL AND POLITICAL BOUNDARIES AND NATURAL CONDITIONS OF THE STATE OF ETTISHAHAR - Ilash o‘g‘li, Abduxamidov Jalol (Journal of Learning on History and Social Sciences, 2025)
Objective: The historical development of East Turkestan in the 19th century is pivotal in understanding the geopolitical dynamics of Central Asia. One significant episode is the rise of the Seven Cities State under Muhammad Yakubbek, formed after consolidating various khanates in East Turkestan amidst regional instability and external imperial interests. Method: This article aims to explore the geographical, political, and administrative structure of the Seven Cities State, its defense strategy, internal governance, and diplomatic efforts to preserve sovereignty against major powers. Result: The study reveals that Muhammad Yakubbek effectively unified the region, structured the state into hierarchical provinces, revived traditional governance mechanisms, and sought international recognition while navigating pressures from Russia, China, and Britain. The research offers a multi-layered analysis of the state's administration, integration strategies, and Muhammad Yakubbek’s pragmatic diplomacy, based on a synthesis of historical narratives. Novelty: The findings highlight the fragile nature of emerging states in contested borderlands and underscore the role of geopolitical foresight, regional alliances, and administrative reform in state survival during imperial rivalries.